Sarvodayanī jīvanakaḷā : racanātmaka nāgarikadharma : Ācārya Ela. Pī. Jêkasakrta "Constructive citizenship" - Jacks, L. P. (Lawrence Pearsall), 1860-1955 (SAMP early 20th-century Indian books project, 1942)
On citizenship and social ethics.